A comparative study on conservative Judaism and Islamic approaches to the reconstruction of religious thought: special focus on selected issues - Abdul Rahim, Adibah; Mohd Daud, Noor Amali (2015)
Conservative Judaism claimed to be in the middle position between orthodox and reform Judaism attempting to maintain basic traditions while adapting to modern life. In its approach to reconstruction of reconstruction of religious thought, this position argued that to meet the challenges of the modern world, the key concepts of faith have to be redefined and reinterpreted. Both Islamic reform and Conservative Judaism shared a similar objective, that is, to reconstruct religious thought in the light of modern science and knowledge. However, both present different views and methods of interpreting scriptures and traditions in the light of new scientific knowledge. This paper highlights selected issues advocated by Conservative Judaism for reconstruction of religious thought, and compares them with Islamic point of views. It was found that despite of claiming themselves as belong to mediating position, Conservative Judaism seemed to ignore their scriptures and depended much on human interpretations, especially in their methods of interpretation of law. This is obviously contradicted to an Islamic approach which upholds that the fundamental sources of the Qur'an and Sunnah should always be referred to as primary references despite our reliance on modern knowledge and rational inquiries. Since the study is theoretical in nature, it is confined to library research. It is hoped that this study will provide a proper understanding on the response of religious thought from the perspective of two different religions, Judaism and Islam.